PERANAN OLAHRAGA REKREASI DALAM KEHIDUPAN SOSIAL - Wahyu Indra Bayu, (Ordik, 2012)
In the Law No. 3 of 2005 section 1, verse 12, sports recreationis a exercise undertaken by peoplewith pleasure and ability which grow and develop in accordance with the conditions and cultural values ​​of local communities for health, fitness, and fun. And one aim is to build social relationships (section 19 verse 3). Recreational activities expanded beyond simple fatigue recovery activities into an activity to gain new experiences for the perpetrators, thus recreational sports has become an important part in public life and advancing to the shape of different purposes, one of the aim is to fulfill  a social function (this social function is performed for group activities).